Gender in the Public Sphere - Bessett, Danielle (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This out of class exercise requires students to choose and attend a talk from a pre-approved list, which they are asked to summarize and assess in a written essay of five pages. Students apply a sociological critique of the uses of "gender" outside the classroom and may explore specific topics in which they are interested (but which we may not be able to address in class).